Weimar surfaces : urban visual culture in 1920s Germany - Ward, Janet, 1963- (University of California Press, 2001)
This study revisits Weimar Germany via the lens of metropolitan visual culture, analyzing the power that 1920s Germany holds for today's visual codes of consumerism.
Keywords: Arts, German -- 20th century.; Modernism (Aesthetics) -- Germany.; Popular culture -- Germany -- Influence.; Germany -- History -- 1918-1933.; Arts allemands -- 20e siècle.; Modernisme (Esthétique) -- Allemagne.; Culture populaire -- Allemagne -- Influence.; Allemagne -- Histoire -- 1918-1933.; ART -- Popular Culture.; ARCHITECTURE -- History -- General.; Arts, German; Modernism (Aesthetics); Popular culture -- Influence; Germany; 1900-1999; Humaniora -- Film.; Humaniora -- Kunst.; Samfundsvidenskab -- Sociologi.; History